2015
DOI: 10.1080/03650340.2015.1049160
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen and wheat residue on cotton (Gossypium hirsutumL.) yield and weed control

Abstract: Wheat (Triticum aestivum L.) residues and nitrogen (N) management are the major problems in the southern part of Iran where irrigated wheat-cotton (Gossypium hirsutum L.)-wheat rotation is a common practice. A 2-year (2009-2011) field experiment was conducted as a split plot design with four replications at a cotton field (Darab), Fars Province, Iran, to determine the influence of different rates of wheat residue (0%, 25%, 50%, and 75%) incorporation and N rates (150, 200, 300, and 400 kg ha −1 ) on weed suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The herbicides and allelopathic aqueous extracts are effective alone and in combination, one of the examples contains purple nut sedge where the extract of allelopathic sorghum (sorgaab) and a modest dosage of smetolachlor have been showed 62 -92 % control (Iqbal and Cheema 2008;Chohan et al, 2020). Kazemeini et al (2016) reported about the usage of crop residues that required for covering soil surface for controlling the problems of soil erosion and reduced the probability of weed growth, because of variation in temperature of soil or soil physical properties for weed seedlings. The largest and lowest reductions in weeds were reported when 75 and 25 % of wheat residues were added to the soil sample correspondingly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The herbicides and allelopathic aqueous extracts are effective alone and in combination, one of the examples contains purple nut sedge where the extract of allelopathic sorghum (sorgaab) and a modest dosage of smetolachlor have been showed 62 -92 % control (Iqbal and Cheema 2008;Chohan et al, 2020). Kazemeini et al (2016) reported about the usage of crop residues that required for covering soil surface for controlling the problems of soil erosion and reduced the probability of weed growth, because of variation in temperature of soil or soil physical properties for weed seedlings. The largest and lowest reductions in weeds were reported when 75 and 25 % of wheat residues were added to the soil sample correspondingly.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its many good properties for example comfort, strengths, retention of color and absorption, fiber of cotton is utilized in various products (Khan et al, 2020). Kazemeini et al (2016) described that cotton plants have an indeterminate growth habit, related to this complexity in growth habit of cotton is sensitive to adverse environmental condition and management practice for example mulching, plant spacing, insect and weed control, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Inequalities ( 2) -( 4) implement the condition under which each crop must be sent where it produces the maximum yield.Such a restriction is introduced for each type of crop, which can be conditionally divided into three groups: the first is cotton, the second is forage crops, the third is corn, wheat and barley. Inequalities (5), ( 6) and ( 7) make it possible to evaluate crops and crop rotations in terms of their labour intensity (5), production costs (7) and the possibility of obtaining gross output (6) on a crop rotation field [12].…”
Section: Methods and Modelsmentioning
confidence: 99%
“…At the second stage, the problem of predicting crop yields of crop rotation fields is solved, taking into account the alternation of cotton and its predecessors for the rotation period. The experience of scientists and the practice of mastering crop rotations in farms show that in the first years of cotton sowing after ploughing alfalfa in crop rotation fields, high yields are obtained, starting from the 3rd and 4th years of sowing, the productivity of the fields decreases, respectively, the yield of cotton also decreases [3][4][5]. This should be taken into account in the model as the main phenomenon that occurs during the alternation of crops in a crop rotation.…”
Section: Introductionmentioning
confidence: 99%
“…These results in agreement with Mahmood et al (2020); Sarlach and Brar (2020) found that different varieties significantly affected number of bolls plant -1 . In addition, Kazemeini et al (2016) told that residues of wheat straw increased number of bolls plant to (24.93). Interaction of all factors on number of bolls/plant in both study sites…”
Section: Effect Of Varieties Plant Spacing and Mulching On Number Of ...mentioning
confidence: 99%